Effects of processing conditions on powder properties of black glutinous rice (Oryza sativa L.) bran anthocyanins produced by spray drying and freeze drying - Laokuldilok T. (Academic Press Inc., 2015)
© 2015 Elsevier Ltd. Black glutinous rice (BGR) was milled and the bran was collected for anthocyanins extraction. The broken rice fraction was enzymatically produced as black glutinous rice maltodextrins (BRM) with 3 dextrose equivalents (DE), including DE10 (BRM10), 20 (BRM20) and 30 (BRM30). The BRMs were used as wall materials in microencapsulation processes. Feed mixtures were spray dried at 3 inlet air temperatures (140, 160 and 180°C) and freeze dried at-45°C. Process yield, anthocyanin retention, and powder properties were investigated. The results demonstrated that increasing the inlet air temperature caused a decrease in the bulk density and anthocyanin retention. Moreover, increasing the inlet air temperature enhanced dehydration, process yield, solubility, dispersibility, flowability and smooth particle surface. The suggested conditions for the spray drying process were 180°C of inlet air temperature combined with BRM20, and the suggested wall material for the freeze drying process was also BRM20. A comparison between the BRMs and a commercial maltodextrin (DE10) showed that microencapsulation of anthocyanin using BRM20 had a higher process yield while the other powder properties were similar. The results suggest that BRM can be applied to replace commercial maltodextrin for anthocyanin microencapsulation.